Inpatient palliative care consultation for patients with glioblastoma in a tertiary hospital. Issue 8 (6th August 2013) - Lin, E.; Rosenthal, M. A.; Eastman, P.; Le, B. H.
Abstract: Glioblastoma (GBM) is an uncommon disease with significant mortality and morbidity, but there is a lack of published evidence on palliative care involvement with this population. This audit highlights the heavy symptom burden, extensive allied health involvement and discharge outcomes of GBM inpatients referred to the palliative care service at The Royal Melbourne Hospital. This information can provide an important framework for further research and also supports the role of multidisciplinary palliative care in the care of patients with GBM.